2019
DOI: 10.1111/hel.12660
|View full text |Cite
|
Sign up to set email alerts
|

Primary and secondary antibiotic resistance of Helicobacter pylori in Korea from 2003 to 2018

Abstract: Background Antimicrobial resistance of Helicobacter pylori (H pylori) affects the efficacy of eradication therapy. The aim of this study was to estimate the prevalence of primary and secondary resistance of H pylori isolates to antibiotics in Korea. Methods The present study was performed from 2003 to 2018. Primary resistance was evaluated in 591 patients without any history of eradication and secondary resistance in 149 patients from whom Helicobacter pylori was cultured after failure of eradication. A minima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 56 publications
(111 reference statements)
5
46
1
2
Order By: Relevance
“…The clarithromycin resistance was greater than 15%, which is consistent with the results from recent studies conducted in Korea [ 16 , 17 ]. This high resistance is probably related to frequent use of clarithromycin for various indications, including upper or lower respiratory tract infections.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The clarithromycin resistance was greater than 15%, which is consistent with the results from recent studies conducted in Korea [ 16 , 17 ]. This high resistance is probably related to frequent use of clarithromycin for various indications, including upper or lower respiratory tract infections.…”
Section: Discussionsupporting
confidence: 92%
“…After the European Committee on Antimicrobial Susceptibility Testing (EUCAST) proposed clinical breakpoints of antibiotics for H. pylori in 2012, including tetracycline, we can now use the breakpoint of >1 mg/mL, just as in this study [ 29 ]. Accordingly, recent studies have also been reporting the increasing trend of tetracycline resistance of H. pylori with the same standards for breakpoints [ 17 , 30 ]. The tetracycline resistance more than doubled over 10 years in Korea, by the clinical breakpoint from the EUSCAST [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although resistance rate to metronidazole is over 30% in Korea, bismuth‐containing quadruple therapy is effective unless the minimum inhibitory concentration (MIC) of metronidazole exceeds 32 μg/mL . Furthermore, H. pylori resistance against tetracycline has been low and stable in Korea for the past 16 years . A recent multicenter study showed that the antibiotic resistance rate in H. pylori is lowest in Seoul .…”
Section: Introductionmentioning
confidence: 99%
“…4 Furthermore, H. pylori resistance against tetracycline has been low and stable in Korea for the past 16 years. 5 A recent multicenter study showed that the antibiotic resistance rate in H. pylori is lowest in Seoul. 6 In that study, the rate of tetracycline resistance was 0%.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] For the antibiotic resistance in H. pylori infection, bacterial culture and disc diffusion method are recommended by the Clinical Laboratory Standard Institute (CLSI). [16][17][18] However, compared with H. pylori culture, molecular pathological detection based on molecular markers, such as real-time polymerase chain reaction (PCR) and conventional PCR analysis, is a very simple and economic approach which also takes less time. Our study was designed to determine the effect and safety of H. pylori eradication therapy based on the results of molecular pathologic antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%